Airway hyperreactivity is frequent in non‐asthmatic children with sickle cell disease. Issue 9 (30th December 2015) - Shilo, Natalie R.; Alawadi, Aceel; Allard‐Coutu, Alexandra; Robitaille, Nancy; Pastore, Yves; Bérubé, Denis; Jacob, Sheila V.; Abish, Sharon; Dauletbaev, Nurlan; Lands, Larry C.
Summary: Background: Asthma is associated with poorer outcomes in sickle cell disease (SCD). Whether AHR can exist in SCD as a distinct entity, separate and independent of asthma, is unknown. Aims: Our goal was to elucidate the prevalence of AHR, as measured by a methacholine challenge test (MCT), in children with SCD who did not have concomitant asthma or any recent history of acute chest syndrome (ACS). To determine if AHR was associated with asthma‐like symptoms, we compared the results of the MCT to a validated asthma questionnaire. We also examined if a correlation between AHR and inflammatory markers exists. Methods: AHR was identified with a positive MCT defined as a provocation concentration (PC20 ) < 4 mg/ml. The children and/or their parents completed the ISAAC (International Study of Asthma and Allergies in Children) questionnaire. We obtained blood, urine, and exhaled breath condensate samples. We measured cysteinyl leukotriene levels in urine and exhaled breath condensate via enzyme immunoassay. Results: Twenty‐nine of forty children (72.5%) had a positive MCT. Nine (31.0%) also reported asthma‐like symptoms on questionnaire. Inflammatory markers did not correlate with AHR. Among MCT positive subjects, those on hydroxyurea had significantly less severe AHR as quantified by PC20 ( P  = 0.014). Conclusions: In children with SCD, there is a high prevalence of AHR that is not associated with asthma‐like symptoms. AHR may be a distinct entity in children with SCD, existing in the absence of concomitant asthma. Hydroxyurea therapy might lessen the severity of AHR in affected individuals.Pediatr Pulmonol. 2016; 51:950–957 . © 2015 Wiley Periodicals, Inc.